The relationship between organisational culture and financial performance: Some South African evidence - W. Z. Van Der Post; T. J. De Coning; E. V.D.M. Smit (South African Journal of Business Management, 1998)
Although statistical evidence seems to be lacking. it is at present widely acknowledged that organisational culture has the potential of having a significant effect on organisational performance. An analysis of sustained superior financial performance of certain American organisations has attributed their success to the culture that each of them had developed. It has been proposed that these organisations are characterised by a strong set of core managerial values that define the ways in which they conduct business. how they treat employees, customers, suppliers and others. Culture is to the organisation what personality is to the individual. It is a hidden but unifying force that provides meaning and direction and has been defined as the prevailing background fabric of prescriptions and proscriptions for behaviour, the system of beliefs and values and the technology and task of the organisation together with the accepted approaches to these. Recent studies have indicated that corporate culture has an impact on a firm's long-term financial performance: that corporate culture will probably be an even more important factor in determining the success or failure of firms in the next decade; that corporate cultures that inhibit long-term financial performance are not rare and that they develop easily. even in firms that are staffed by reasonable and intelligent people; and that corporate cultures, although difficult to change, can be made more performance enhancing. The purpose of this study, therefore, was to establish the statistical relationship between organisational culture and financial performance.
Keywords: 650